A Socio-pragmatic Study of the Speech Act of Divorce in Religious and Legislative Discourse - Hani Zaidan , Maha; Aliwy Mohammed , Hashim (Journal of College of Education, 2020)
Linguistic studies attempt to cover all issues, whether social, legal, linguistic, medical or even technological. Since social issues are the most important issues that need to be focused on, this study is devoted to analyse one distinctive social issue i.e., divorce Hence, divorce, as a main important social issue, is a controversial topic, since it varies among religions and cultures, in addition to its different legislations among countries. Therefore, this study attempts to analyse socio-pragmatically the speech act of divorce in religious and legislative texts, namely, the Quranic and Biblical texts and legislations of both Iraq and Britain. This study aims to examine the socio-pragmatic factors that influence divorce in religious and legislative texts and to compare between the two languages in terms of divorce socio-pragmatically in religious and legal laws. The researchers use a qualitative method of research. The model employed in this study is that of Austin’s felicity conditions (1965) and Grice’s cooperative principle (1975). The results of this study reveal that socio-pragmatic factors have an essential role on affecting, performing and expressing divorce across religions and cultures. It is also found that the same speech act is performed differently across cultures employing different felicity conditions while submitting to the same maxims with different results.